PENINGKATAN KETERAMPILAN MEMBACA PUISI DENGAN MENGGUNAKAN MEDIA AUDIO VISUAL - Neni Tri Andari (Universitas Wijaya Kusuma Surabaya, 2023)
Poetry is a literary work that has specificity, both in terms of language, word choice, and readers. Indonesian language learning in poetry reading material at SMP Negeri 3 Kubu Babussalam One Roof, Rokan Hilir Regency, Riau has so far been less favored, because students are less motivated and lack self-confidence when reading poetry. The author seeks to improve these conditions by conducting learning using audio-visual media in learning to read poetry. The problem discussed in this scientific work is how the process of improving poetry reading by using audio-visual media in class VIII of SMP Negeri 3 Kubu Babussalam One Roof. The aim is to find out the process of improving poetry reading skills using audio-visual media in class VIII of SMP Negeri 3 Kubu Babussalam One Roof, Rokan Hilir Regency, Riau.